Validação e Normatização do Questionário de Diagnóstico Adaptativo Operacionalizado (QDAO) - Farhat, Cecilia Aparecida Vaiano (2019)
This study aimed to look for evidence of validity and standardization for the Operationalized Adaptive Diagnostic Questionnaire, which evaluates Adaptive Effectiveness in a specific pop- ulation of college students. In order for this instrument to be applied to a population of individ- uals over 18 years old, both sexes and with a minimum level of complete high school, there is a need for reevaluation. Adaptive effectiveness is understood as the degree of adaptation of the individual, arising from the coherence between their internal values and the values of the culture in which they live. The concept of adaptation is subdivided into four aspects: Relational Affec- tive, Productivity, Sociocultural and Organic. Initially, the 210 items that made up the QDAO were reassessed by four expert judges (content analysis) to verify which sectors of the adapta- tion the items belonged to. Only items with agreement between the judges greater than or equal to 80% were maintained; thus, the instrument was reduced to 178 items; Then the semantic analysis was performed, after which the instrument was finished with 177 items. Therefore, the new instrument, with 177 items, has content validity to evaluate the adaptation considering that the individual and global Kappa indices reached values greater than 85%, above the standard established by the literature of 80%. In possession of the new instrument, data were collected through the Google-drive online platform. 489 people participated, being 42.94% aged 19 to 23 years, totaling 78% between 18 to 33 years (n = 380). Most were women 73% (n = 355), 49.7% had high school; singles represented 72% (n = 351), most with family incomes of up to 5 min- imum wages, 39% (n = 192) and between 5 and 10 minimum wages 35% (n = 168); Most participants were from the southeast region (79.6%). The data comprised a spreadsheet and were analyzed by the RStudio software, through which the validity indicators were analyzed and the new QDAO standardized. Multidimensional Item Response Theory (IRT) was used with the bfactor methodology. The results revealed that 60 items could explain the construct and point out that the model presents reasonable adjustment indices (M2 = 3434,626 (p <0.05), RMSEA = 0.0523 with 95% confidence interval = [0.050007; 0.054555], SRMSR = 0.0670, TLI = 0.7916, CFI = 0.8073) and overall reliability was 0.82, but only the AR sector obtained an acceptable value (0.78), but is being proposed the model with 32 items and the AR sector. Which items discriminate each sector of adaptation were pointed out. It was proposed a stand- ardization that uses the interquartile range limit criterion to detect individuals with some prob- lem in some adaptation sector observing the values that are outside this interquartile range. Comparisons with other structures identified in the literature revealed some similarities regard- ing the identified dimensions, although there are differences in the composition of the items. Only one dimension has acceptable reliability index. Problems are pointed out in the study and a research agenda is suggested.